2019
DOI: 10.3390/rs11040374
|View full text |Cite
|
Sign up to set email alerts
|

Improved Automated Detection of Subpixel-Scale Inundation—Revised Dynamic Surface Water Extent (DSWE) Partial Surface Water Tests

Abstract: In order to produce useful hydrologic and aquatic habitat data from the Landsat system, the U.S. Geological Survey has developed the “Dynamic Surface Water Extent” (DSWE) Landsat Science Product. DSWE will provide long-term, high-temporal resolution data on variations in inundation extent. The model used to generate DSWE is composed of five decision-rule based tests that do not require scene-based training. To allow its general application, required inputs are limited to the Landsat at-surface reflectance prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
142
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(142 citation statements)
references
References 50 publications
0
142
0
Order By: Relevance
“…This study builds on prior studies of open water classification [11,61,62] and area distribution scaling [6,23,63] using spaceborne and airborne color-infrared digital imagery by: (1) advancing a new, high-resolution AirSWOT color-infrared (CIR) camera dataset and open water classification for the NASA Arctic-Boreal Vulnerability Experiment (ABoVE); (2) applying the connectivity-preserving binarization technique [47] and an object-based framework to classify open water in the CIR dataset;…”
Section: Discussionmentioning
confidence: 99%
“…This study builds on prior studies of open water classification [11,61,62] and area distribution scaling [6,23,63] using spaceborne and airborne color-infrared digital imagery by: (1) advancing a new, high-resolution AirSWOT color-infrared (CIR) camera dataset and open water classification for the NASA Arctic-Boreal Vulnerability Experiment (ABoVE); (2) applying the connectivity-preserving binarization technique [47] and an object-based framework to classify open water in the CIR dataset;…”
Section: Discussionmentioning
confidence: 99%
“…Creed et al [23] suggested that the coupling of digital terrain analyses with remote-sensing techniques could enhance our ability to characterize dynamic hydrologic parameters such as soil moisture. For example, satellite detection of surface water using Landsat or Synthetic-aperture radar imagery (e.g., Dynamic Surface Water Extent, Global Surface Water Explorer) are available at 8-to 16-day time steps, thus providing an opportunity to generate wetland maps that capture dynamic inter-and intra-annual hydrologic transitions [56][57][58].…”
Section: Extrapolating Fluxesmentioning
confidence: 99%
“…In addition to the agricultural lands and NDVI masks, a mask was also applied to remove water-covered areas using the Dynamic Surface Water Extent product [39]. Any pixel that was identified as open water during a calendar year was masked out.…”
Section: Masking Landsat Imagery To Non-vegetated Croplandsmentioning
confidence: 99%